Pengaruh Inovasi Produk Dan Orientasi Pasar Terhadap Kinerja Pemasaran Dimediasi Keunggulan Bersaing - Anna Damayanti; Endang Tjahjaningsih (Universitas Muhammadiyah Sorong, 2023)
This examines goals to decide the effect of product innovation and market organization on marketing performance. Quantitative descriptive methods were used in this study, with the populace on this observe being UMKM withinside the meals enterprise sector in Central Java Province with a total of 105 people. The analysis in this study used validity tests, reliability tests, and model tests which included regression tests, coefficient of determination tests, simultaneous significance, and mediation tests using SPSS 21.0 software. From the results of this analysis and discussion it shows that product innovation and market orientation have a good and large influence on competitive advantage, in addition to product innovation and market orientation which even have a good and large influence on marketing performance, from the consequences of competitive advantage studies they also have a subtle and good impact on marketing performance. In addition, competitive advantage is proven to be a mediator between product innovation and market orientation towards marketing performance.